2021
DOI: 10.1001/jamanetworkopen.2021.0380
|View full text |Cite
|
Sign up to set email alerts
|

Association of Supporting Trial Evidence and Reimbursement for Off-Label Use of Cancer Drugs

Abstract: Key Points Question Is evidence from randomized clinical trials associated with the reimbursement decisions that determine access to off-label use of cancer drugs in Switzerland? Findings In this cross-sectional study including 3046 patients with cancer, there were a total of 695 off-label use requests for 598 patients (20%). A total of 67% of requests were reimbursed when supporting trials showed overall survival benefit, but 65% of requests were reimburse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
0
15
0
2
Order By: Relevance
“…Swissmedic approved nivolumab for this indication 1 year later in August 2018. Within this year, nivolumab was requested 14 times as OLU for the adjuvant treatment of localised melanoma in our cohort (see also Herbrand et al 4). Another example is pembrolizumab, which was requested nine times as first-line treatment for metastatic non-small lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Swissmedic approved nivolumab for this indication 1 year later in August 2018. Within this year, nivolumab was requested 14 times as OLU for the adjuvant treatment of localised melanoma in our cohort (see also Herbrand et al 4). Another example is pembrolizumab, which was requested nine times as first-line treatment for metastatic non-small lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the use of a drug is off-label may vary across different countries and can change over time 3. In Switzerland, about 20% of patients with cancer are treated at least once with OLU 4. Situations in which OLU is intended include those when heavily pretreated patients do not have any further approved treatment option,5 or when randomised evidence for new and beneficial treatment options becomes available but formal approval is pending,6 7 or when treatment strategies from other cancer types are extrapolated to the specific case 8.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Herbrand, A.M. Schmitt, M. Briel, et al in years 2015-2018. Research conducted in a Swiss population demonstrated that 45% of first line treatment cases in a group of 3046 patients treated for cancer was associated with a decision to implement off-label treatment [9]. In a study published in 2021, Japanese researchers demonstrated that diseases most commonly treated off-label were sarcoma, urologic cancers, and gastrointestinal cancers [10].…”
Section: Admissibility Of Off-label Use Of Medicinal Products In Onco...mentioning
confidence: 99%